Ответ:
Объяснение:
N(H2O) = Na *n =6*10²³ * 3 = 1,8*10²⁴ молекул
N(H2O) = Na*n = 6*10²³*0,5 = 3*10²³ молекул
N(H2O) = Na*n = 6*10²³ * 4 = 2,4*10²⁴ молекул
N(H2O) = Na*n = 6*10²³*0,1 = 6*10²² молекул
N(H2O)= Na*n = 6*10²³*5 = 3*10²⁴ молекул
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
N(H2O) = Na *n =6*10²³ * 3 = 1,8*10²⁴ молекул
N(H2O) = Na*n = 6*10²³*0,5 = 3*10²³ молекул
N(H2O) = Na*n = 6*10²³ * 4 = 2,4*10²⁴ молекул
N(H2O) = Na*n = 6*10²³*0,1 = 6*10²² молекул
N(H2O)= Na*n = 6*10²³*5 = 3*10²⁴ молекул